PSILOCYBIN IN PSYCHIATRIC PRACTICE AND PSYCHEDELIC-ASSISTED THERAPY FOR TREATMENT-RESISTANT DEPRESSION - Łukasz Deska; Cezary Kosmecki; Dawid Głaz; Natalia Kamińska; Wojciech Sołtys; Magdalena Stolarczyk; Maksymilian Głaz; Mateusz Stronczyński; Aleksandra Jagura-Sukiennik; Julia Wawerska (International Journal of Innovative Technologies in Social Science, 2026)
This manuscript comprehensively reviews psilocybin-assisted therapy for major depressive disorder and treatment-resistant depression. It aims to synthesize current understanding regarding its mechanisms, efficacy, safety, costs, and accessibility, comparing it with conventional antidepressant and ketamine treatments. The methodology involved a narrative synthesis of academic literature, drawing from systematic reviews, meta-analyses, and clinical trials identified through targeted database searches.Key findings indicate that psilocybin therapy demonstrates rapid, robust, and sustained antidepressant effects, with high response and remission rates, often after one or two sessions. Its safety profile is generally favorable, with transient and mild adverse events. Mechanistically, psilocybin primarily acts on serotonin 5-HT2A receptors, modulating brain networks and enhancing neuroplasticity. However, significant challenges exist in terms of high costs, limited accessibility due to the intensive therapeutic model, and regulatory hurdles.In conclusion, psilocybin-assisted therapy offers a promising alternative for depression, particularly where standard treatments fail, by providing rapid and durable symptom reduction through unique neurobiological pathways. Future research should focus on optimizing treatment protocols, exploring long-term outcomes, identifying predictors of response, and addressing systemic barriers to accessibility and cost-effectiveness to facilitate its integration into broader mental healthcare.